PENGARUH HATHA YOGA TERHADAP PENURUNAN TINGKAT STRES PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TINGKAT AKHIR - Syauqiyyah Alyaa Hamsya (2022)
Stress is a condition that occurred when someone is under pressured. This caused by unbalanced activities, self-pressure, and anxiety. Everyone might have this kind of condition as well as final year medical students who are currently working on their thesis. Stress can be reduced by doing some meditation such as yoga. One of the method commonly used in yoga is Hatha Yoga. This method is slowly paced and focused on breathing, controlled movement, and body stretching at the end. The main purpose of this study is to determine the effect of Hatha Yoga on reducing stress levels in final year medical students. This study is using the true experiment method with Pre-test & Post-test with Control Group Design, consisting of 18 respondents for each intervention and control group. This study used simple random sampling method and Paired T Test and Independent T Test data analysis. Statistical analysis results using Paired T Test showed that there is significant mean different on intervention group before and after doing the Hatha Yoga with p-value 0.000 < 0.05. Meanwhile, there is no significant mean changing with p-value 0.688 > 0.05. Independent T Test showed a significant change between intervention and control group with p-value 0.000 < 0.05. This conclude that there is an effect of Hatha yoga in reducing stress levels. This study shows that Hatha Yoga is effective and could be an non-pharmacological alternatives on reducing stress levels.